PENGEMBANGAN PORTAL DIGITAL WISATA KABUPATEN MUARA ENIM BERBASIS WEBSITE - Maya Anggita; Leon A. Abdillah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The development of information technology has encouraged the use of websites as platforms for delivering information and promotion, including in the tourism sector. Muara Enim Regency has various tourism destinations, yet the available information is scattered across unofficial sources, making it difficult for tourists to obtain accurate and reliable data. This research aims to design and develop a web-based digital portal that provides comprehensive, accurate, and easily accessible tourism information for Muara Enim Regency. The system was developed using the Extreme Programming (XP) method, which emphasizes iterative and flexible development. The implementation results show that the website successfully presents tourism information through features such as destination descriptions, photo galleries, tourism categories, location details, and a content management system for administrators. System testing was conducted using the blackbox method, and all test scenarios produced results that matched the expected functionality without any errors and The results of usability testing using SUS obtained a score of 81.9 which is included in the Acceptable category with Grade A. Therefore, the developed website is considered feasible to serve as an information and promotional medium for tourism, helping tourists obtain valid information and supporting the local Tourism Office in enhancing the attractiveness of regional destinations.